Associations of ARMS2 and CFH Gene Polymorphisms with Neovascular Age-Related Macular Degeneration - Supanji S; Romdhoniyyah DF; Sasongko MB; Agni AN; Wardhana FS; Widayanti TW; Prayogo ME; Perdamaian ABI; Dianratri A; Kawaichi M; Oka C (Clinical Ophthalmology, 2021)
Supanji Supanji,1– 4 Dewi Fathin Romdhoniyyah,1,2 Muhammad Bayu Sasongko,1,2,4 Angela Nurini Agni,1,2,4 Firman Setya Wardhana,1,2,4 Tri Wahyu Widayanti,1,2,4 Muhammad Eko Prayogo,1,2,4 Ayudha Bahana Ilham Perdamaian,1,2 Aninditta Dianratri,1,2 Masashi Kawaichi,5 Chio Oka5 1Department of Ophthalmology, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada, Yogyakarta, Indonesia; 2Department of Ophthalmology, Dr. Sardjito General Hospital, Yogyakarta, Indonesia; 3Ophthalmology Clinic, Military Air Force Central Hospital Dr. Suhardi Hardjolukito, Yogyakarta, Indonesia; 4Ophthalmology Clinic, Dr YAP Eye Hospital, Yogyakarta, Indonesia; 5Laboratory of Gene Function in Animals, Nara Institute of Science and Technology, Ikoma, Nara, JapanCorrespondence: Supanji SupanjiDepartment of Ophthalmology, Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada, Jalan Farmako Sekip Utara, Yogyakarta, 55281, IndonesiaTel +62 274 560300Fax +62 274 581 876Email supanji@ugm.ac.idPurpose: This study aimed to determine the association of ARMS2 A69S, ARMS2 del443ins54, and CFH Y402H polymorphisms with neovascular age-related macular degeneration (nAMD) for the first time in an Indonesian population.Patients and Methods: Our case–control study involved 104 nAMD and 100 control subjects. AMD diagnosis was evaluated by retinal specialists based on color fundus photography and optical coherence tomography. The polymorphisms on CFH Y402H and ARMS2 A69S were analyzed by PCR-restriction fragment length polymorphism (PCR-RFLP), whereas ARMS2 del443ins54 was evaluated by PCR-based assay.Results: Significant allelic associations with nAMD were detected on all polymorphisms (P< 0.05), with stronger association with the ARMS2 A69S (OR 3.13; 95% CI 2.08– 4.71; P< 0.001) and ARMS2 del443ins54 (OR 3.28; 95% CI 2.17– 4.95; P< 0.001) polymorphisms than with CFH Y402H (OR 2.08; 95% CI 1.08– 3.99; P=0.028). Genotype analysis showed a statistical difference between nAMD and the control group for all polymorphisms (P< 0.05). However, the association with nAMD was weaker for CFH Y402H (P=0.043) than for ARMS2 A69S and ARMS2 del443ins54 (P< 0.001). A significant interaction between ARMS2 A69S and hypertension was documented (OR 9.53; 95% CI 3.61– 25.1; P< 0.001).Conclusion: Our findings indicate that ARMS2 A69S and ARMS2 del443ins54 polymorphisms are strongly associated with the risk of nAMD for the first time in an Indonesian population. The risk of nAMD increased when the presence of risk alleles from ARMS2 A69S was combined with the presence of hypertension.Keywords: age-related macular degeneration, ARMS2, CFH, polymorphism